The Legal Perspectives on Driving Economic Growth: A Study of Strategic Plan Implementation in East Kalimantan - Gusti Naufal Rizky Perdana; Abdul Hakim; Suryadi Suryadi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
This study aims to describe and analyze the Strategic Plan (RENSTRA) implementation process for East Kalimantan Province to strengthen economic growth. The research adopts a qualitative approach involving steps such as formulating research questions, collecting primary data through interviews and observations, and analyzing data using the interactive model developed by Miles and Huberman. The research focuses on policy implementation aspects such as clarity of standards and objectives, resource allocation, and inter-organizational coordination. The East Kalimantan Regional Development Planning Agency (BAPPEDA) serves as the locus of the study, with the selection of primary data involving key informants and informants through purposive sampling techniques. The findings indicate the commitment and efforts made by BAPPEDA to achieve regional economic development goals through the implementation of RENSTRA. However, challenges such as limited human resources, budget allocation, and consistency in inter-organizational communication still need to be addressed. The limitations of this study include its focus on East Kalimantan Province, which limits the generalizability of the findings. Further research could expand the scope to compare RENSTRA implementations in other regions or more deeply explore factors affecting policy implementation performance. It is hoped that future research will provide deeper insights and more effective solutions to enhance regional economic growth in East Kalimantan and other areas